2023
DOI: 10.1111/jnc.15827
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of short‐chain fatty acids against oxidative stress‐induced SH‐SY5Y injury via GPR43‐dependent pathway

Abstract: A neurodegenerative disorder is a condition that causes a degeneration of neurons in the central nervous system, leading to cognitive impairment and movement disorders. An accumulation of oxidative stress in neurons contributes to the pathogenesis of neurodegenerative disorders. Over the past few years, several studies have suggested that short-chain fatty acids, metabolites of the gut microbiota, might have a beneficial effect in neurodegenerative disorders. A G protein-coupled receptor 43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…SCFAs are the essential metabolic products of oligosaccharides fermented by intestinal microorganisms. It has been reported that SCFAs have a variety of physiological functions and a wide range of applications in the treatment of diseases (Li et al ., 2023; Saikachain et al ., 2023). The composition and concentration of SCFAs in the control group, FOS group, and GMOS group during in vitro fermentation are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SCFAs are the essential metabolic products of oligosaccharides fermented by intestinal microorganisms. It has been reported that SCFAs have a variety of physiological functions and a wide range of applications in the treatment of diseases (Li et al ., 2023; Saikachain et al ., 2023). The composition and concentration of SCFAs in the control group, FOS group, and GMOS group during in vitro fermentation are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies focused on GPR41/GPR43 functions suggest their role in modulating oxidative stress and inflammation in various tissues, including neuronal cells. Some studies investigated the protective role of SCFAs and GPR41 activation against oxidative stress-induced neuronal cell injury ( Saikachain et al ., 2023 ) ( Fig. 1D ).…”
Section: Scfas From the Gut Microbiomementioning
confidence: 99%